Mapping the impacts of recent natural disasters and technological accidents in Europe (Luxembourg, 2004)
"This publication is to address the impacts of natural disasters and technological accidents across Europe. Focusing on major events between 1998 and 2002, the report adds value to existing studies by bringing together available information on their human and economic costs and adding the environmental perspective. The impacts of these events are documented through a large number of maps, illustrations and case studies. "